Knowledge, Information and Creativity Support Systems : Selected Papers from KICSS’2014 - 9th International Conference, held in Limassol, Cyprus, on November 6-8, 2014 /: Selected Papers from KICSS’2014 - 9th International Conference, held in Limassol, Cyprus, on November 6-8, 2014. (2016) - Unknown
No abstract available